2011
DOI: 10.1038/hr.2011.98
|View full text |Cite
|
Sign up to set email alerts
|

High-normal blood pressure is associated with microalbuminuria in the general population: the Watari study

Abstract: Microalbuminuria, for which hypertension and diabetes are well-known risk factors, has recently been used to detect individuals at risk for cardiovascular and chronic kidney diseases in the general population. We aimed to determine the thresholds of blood pressure or blood glucose concentration at which the odds ratio of having microalbuminuria begins to increase. An annual public health checkup was conducted on 3166 participants aged 29-84 years (mean, 61 ± 11 years; 40% men) living in Watari town, Japan. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 28 publications
0
17
0
Order By: Relevance
“…In a recent cross-sectional study of the general population using the same cohort as used in the present study [13], we reported that compared to optimal blood pressures, high-normal blood pressures are associated with significantly increased odds ratios (ORs) for the prevalence of microalbuminuria. The causal relationship remained uncertain because of the cross-sectional design of that study.…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…In a recent cross-sectional study of the general population using the same cohort as used in the present study [13], we reported that compared to optimal blood pressures, high-normal blood pressures are associated with significantly increased odds ratios (ORs) for the prevalence of microalbuminuria. The causal relationship remained uncertain because of the cross-sectional design of that study.…”
Section: Introductionmentioning
confidence: 84%
“…Fasting blood sugar levels were determined using a Hitachi 7700P apparatus (Hitachi, Tokyo, Japan). The remaining biochemical markers were determined using a standard automatic analyzer (7700DD; Hitachi) [13]. The estimated glomerular filtration ratio (eGFR) was calculated using the formula provided by the Japanese Society of Nephrology [14]: eGFR (ml/min per 1.73 m 2 ) ¼ 194 Â creatinine À1.094 Â age À0.287 Â (0.739 if female).…”
Section: Measurementsmentioning
confidence: 99%
“…25 The RATIONAL study tackled hypertension management and diabetes in patients with kidney damage in KSA, given the tight reciprocal influence between these conditions. 25,26 It aimed at identifying patterns of pharmacological management of hypertension and its modulation of microalbuminuria evolution over 1 year, by determining the correlation between the beneficial effect of BP control and ACR levels in hypertensive patients in general and with diabetes in particular. About three-quarters of the study patients were males, matching worldwide hypertension prevalence among the male gender; 27 80% of study patients had diabetes and best represented the overall study population.…”
Section: Discussionmentioning
confidence: 99%
“…This study was conducted as a part of the Watari study, a community-based cohort study aimed at examining the association between qualitative and quantitative job stress and cardiovascular diseases. Detailed descriptions of the study have been provided previously 8,9) . The study protocol was approved by the ethics committee of Tohoku Rosai Hospital, and all the participants provided written informed consent.…”
Section: Methodsmentioning
confidence: 99%
“…Detailed descriptions of the study have been provided previously 8,9) . The study protocol was approved by the ethics committee of Tohoku Rosai Hospital, and all the participants provided written informed consent.…”
Section: Methodsmentioning
confidence: 99%